2021
DOI: 10.1186/s12889-021-10731-x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic distress among Syrian refugees with residence permission in Germany: analysis of a cross-sectional register-based study

Abstract: Background Previous studies have already proven high rates of common mental disorders in Syrian refugees. Nevertheless, little is known about the patterns of somatic distress among this refugee population. For this reason, we aimed to examine the prevalence, co-occurrence, and risk factors of somatic distress among Syrian refugees in Germany. Methods This study analyzes the second measurement point (N = 116) of a prospective register-based survey a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 71 publications
3
12
1
Order By: Relevance
“…The models may have been too complex for our data given sample size restrictions. However, this may be a problem that researchers face in refugee studies because of typically small sample sizes due to practical constraints ( Borho et al, 2021 ). It, thus, remains open whether a general somatization factor in a model that additionally accounts for the variance by specifying specific orthogonal factors reduces biases in total scores meaningfully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The models may have been too complex for our data given sample size restrictions. However, this may be a problem that researchers face in refugee studies because of typically small sample sizes due to practical constraints ( Borho et al, 2021 ). It, thus, remains open whether a general somatization factor in a model that additionally accounts for the variance by specifying specific orthogonal factors reduces biases in total scores meaningfully.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical presentations and epidemiological research also highlight the role of somatic symptoms that remain medically unexplained among refugees ( Hassan et al, 2015 ; Nesterko et al, 2020 ). In fact, somatic symptoms are common among Syrian refugees ( Borho et al, 2021 ) and play a central role in their mental health symptom constellations ( Schlechter, Wilkinson, et al, 2021 ).…”
mentioning
confidence: 99%
“…Recently, he also experienced potentially traumatic events. In all vignettes, the described person visited a general practitioner because of somatic complaints (e.g., headache, stomach pain), matching the fact that many Syrian refugees in Germany report somatic symptoms that are medically unexplained (Borho et al, 2021). When no organic causes for the complaints could be identified, the general practitioner referred them to a psychotherapist for a mental health examination.…”
Section: Methodsmentioning
confidence: 99%
“…Patients' expectations of mental health treatment, including therapeutic content, may critically influence APPH. Refugees often report symptoms related to anxiety, depression, sleep problems, somatization, and traumatic stress (Borho et al, 2021;Henkelmann et al, 2020;Lies et al, 2021). Especially two forms of mental health treatment appear effective for such symptoms, namely (1) trauma-focused therapy to deal with emotional consequences of traumatic events (Bisson et al, 2007) and ( 2) skill training that provides practical coping strategies for stressful situations or sleep problems (Van Heemstra et al, 2019).…”
Section: Therapy Contentmentioning
confidence: 99%
“…Among these post-migration stress factors, discrimination is one of the most burdening, significantly worsening the health and well-being of young people with migration background [5]. Research with adult as well as immigrant and refugee youth underscores the negative impact of discrimination on both physical (e.g., self-rated, hypertension, cardiovascular, respiratory) and mental health (affective disorders, e.g., anxiety, depression) [6][7][8]. A recent study among 1366 refugee and non-refugee migrant young people in five European countries revealed that perceived discrimination was associated with increased levels of mental health problems and lower overall well-being for refugees and nonrefugee migrants.…”
Section: Introductionmentioning
confidence: 99%